Can high pain intensity and catastrophizing interfere with the cognitive performance of women with chronic pain related TMD? A cross-sectional study - Melissa de Oliveira MELCHIOR; Luiza Guilherme ANTUNES; César BATAGLION; Laís Valencise MAGRI (University of São Paulo, 2023)
Abstract Interventions based on pain education and self-management are dependent on factors such as attention, memory, concentration, and executive function. Objective To explore the relationship between cognitive performance and the variables pain intensity, central sensitization, catastrophizing, and hypervigilance in women diagnosed with chronic pain-related TMD. Methodology This is a cross-sectional study. A total of 33 women (mean age: 38±4.6 years; range: 18 to 66 years) with chronic pain-related TMD (myalgia and/or arthralgia) diagnosed according to the Diagnostic Criteria for Temporomandibular Disorders (DC/TMD). Specific questionnaires were used to evaluate cognitive performance, overall pain intensity, central sensitization, hypervigilance, and pain catastrophizing. The data were analyzed using Pearson's correlation coefficient and backward stepwise multiple linear regression (statistical significance at 5% alpha). Results Approximately 53% of the study sample showed decreased cognitive performance. High central sensitization, hypervigilance, and pain catastrophizing were observed. A significant negative correlation was observed between cognitive performance and hypervigilance (p=.003, r=−.49), cognitive performance and catastrophizing (p<.001, r=−.58), and cognitive performance and pain intensity (p<.001, r=−.58). Regarding the partial regression coefficients, only catastrophizing and pain intensity showed statistical significance (t=−2.12, p=.043; t=−2.64, p=.014, respectively), indicating a significant role in explaining cognitive performance at the sample. Conclusion High pain intensity and the presence of catastrophic thoughts regarding pain can predict impaired cognitive performance in women with chronic pain-related TMD. Management strategies addressing psychosocial dimensions such as reducing catastrophizing and ensuring complete understanding of the condition are important.